IDENTIFIKASI SURFAKTIN PADA PSEUDOMONAS FLUORESCENS ST1 PENGENDALI EFEKTIF PENYAKIT PUSTUL KEDELAI - Suskandini Ratih Dirmawati . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2009)
Identification of surfactin in Pseudomonas fluorescens ST1 which effectively suppres soybean bacterial pustule. Identification of surfactin in Pseudomonas fluorescens ST1 filtrate was conducted in Plant Pest and Disease Laboratory, Bogor Agriculture University. The 48 hours cultured suspension of P. fluorescens ST1 with 108 CFU/ml density was centrifuged to obtain the supernatant. The supernatant was analyzed for its surfactin content by High Performance Liquid Chromatography with Colum ODS-5 and eluen acetonitril and acetat acid. The result showed that surfactin was producted by P. fluorescens ST1 and this bioactive substance could suppres the bacterial pustule on soybean.